2023
DOI: 10.3390/rs15163927
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Ecological Service Value and Ecological Compensation in Arid Area: A Case Study of Ecologically Vulnerable Oasis

Abstract: In recent years, the delicate balance between economic development and ecological environment protection in ecologically fragile arid areas has gradually become apparent. Although previous research has mainly focused on changes in ecological service value caused by land use, a comprehensive understanding of ecology–economy harmony and ecological compensation remains elusive. To address this, we employed a coupled deep learning model (convolutional neural network-gated recurrent unit) to simulate the ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Remote Sens. 2024, 16, x FOR PEER REVIEW 3 of 20 complex, and adapt to local conditions [24]. Thus, this study considered the characteristics of the Tuha Basin and evaluated the driving force behind oasis variation.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Remote Sens. 2024, 16, x FOR PEER REVIEW 3 of 20 complex, and adapt to local conditions [24]. Thus, this study considered the characteristics of the Tuha Basin and evaluated the driving force behind oasis variation.…”
Section: Study Areamentioning
confidence: 99%
“…Liu et al [12] also found that human factors are the main driving force of landscape pattern changes in Jinghe County. However, human factors are multiple, complex, and adapt to local conditions [24]. Thus, this study considered the characteristics of the Tuha Basin and evaluated the driving force behind oasis variation.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been widely used to assess the degree of coordination between ecology and economy. In [55], they studied the scope of ecological compensation in a fragile oasis in China by measuring the ecological-economic coordination index. According to this model, [56] conducted a quantitative study on the level of ecological-economic harmony in Harbin by quantifying land use/cover change (LUCC).…”
Section: Introductionmentioning
confidence: 99%
“…The Wuwei Oasis is a typical area of complex human-land relations in China [36], and the results of the sixth survey on desertification and sanding in China in 2019 clearly show that the area around the Hexi Corridor in China is home to some of the most severe desertification and sanding in the country [37]. There are 20,800 square kilometers of decertified land and 15,100 square kilometers of non-decertified land in Wuwei, accounting for 64.4% and 46.7% of Wuwei's land area, respectively [38]. In addition, Wuwei is an important energy corridor for transporting clean energy from Northwest China to the Middle East [39].…”
Section: Introductionmentioning
confidence: 99%